2021
DOI: 10.1021/acs.jnatprod.1c00367
|View full text |Cite
|
Sign up to set email alerts
|

Sinularamides A–G, Terpenoid-Derived Spermidine and Spermine Conjugates with Casitas B-Lineage Lymphoma Proto-Oncogene B (Cbl-b) Inhibitory Activities from a Sinularia sp. Soft Coral

Abstract: An extract of a Sinularia sp. soft coral showed inhibitory activity against the E3-ubiquitin ligase casitas B-lineage lymphoma proto-oncogene B (Cbl-b). Subsequent bioassay-guided separation of the extract provided a series of terpenoid-derived spermidine and spermine amides that were named sinularamides A–G (1–7). Compounds 1–7 represent new natural products; however, sinularamide A (1) was previously reported as a synthetic end product. The structures of sinularamides A–G (1–7) were elucidated by analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…526 A number of simple lipids and quinonoid MNPs were reported from cnidarians including dendronephthyones A–C 1171–1173 isolated from a Vietnamese collection of Dendronephthya mucronata , 527 a simple epoxy-derivative of flexibilisquinone 1174 from southern Taiwan specimens of Sinularia scabra , 528 the related hydroquinone sarcotenuhydroquinone 1175 from Sarcophyton tenuispiculatum (cultured specimens), 529 and a series of terpenoid amide derivatives of spermidine and spermine sinularamide A–G 1176 , 1177 , 1178 and 1179–1182 isolated from Sinularia sp. 530 Sinularamide C exhibited weak inhibition of casitas B-lineage lymphoma proto-oncogene B with a potential role of enhancing the adaptive and innate immune system with implications for antitumour immunotherapies. Three compounds reported from the marine environment for the first time, purified from extracts of Sarcophyton trocheliophorum , include a known leachate from plastic pipes 1183 , a phenol previously reported from terrestrial plants 1184 and the wax 1185 .…”
Section: Cnidariansmentioning
confidence: 99%
“…526 A number of simple lipids and quinonoid MNPs were reported from cnidarians including dendronephthyones A–C 1171–1173 isolated from a Vietnamese collection of Dendronephthya mucronata , 527 a simple epoxy-derivative of flexibilisquinone 1174 from southern Taiwan specimens of Sinularia scabra , 528 the related hydroquinone sarcotenuhydroquinone 1175 from Sarcophyton tenuispiculatum (cultured specimens), 529 and a series of terpenoid amide derivatives of spermidine and spermine sinularamide A–G 1176 , 1177 , 1178 and 1179–1182 isolated from Sinularia sp. 530 Sinularamide C exhibited weak inhibition of casitas B-lineage lymphoma proto-oncogene B with a potential role of enhancing the adaptive and innate immune system with implications for antitumour immunotherapies. Three compounds reported from the marine environment for the first time, purified from extracts of Sarcophyton trocheliophorum , include a known leachate from plastic pipes 1183 , a phenol previously reported from terrestrial plants 1184 and the wax 1185 .…”
Section: Cnidariansmentioning
confidence: 99%
“…In order to maintain the balance between the potency and selectivity of the drugs and ensure that the targeted drugs have better efficacy and safety, further evaluation in various screening models is essential. Kinome screening is a significant indicator to assess the selectivity of 139 Subsequent bioassay-guided isolation of extracts provided seven prenylated spermidine or spermine derivatives, which were named sinularamides 1−7. Compounds 1−7 are entirely novel natural products with a highly similar skeleton, consisting mainly of an amide side chain containing positive ammonium ions and an aliphatic acid side chain (Figure 5).…”
Section: Cbl-b Immuno-oncology Agents In Preclinical and Clinic Studiesmentioning
confidence: 99%
“…Recent studies have shown that an extract of the soft coral Sinularia sp. had inhibitory effect on Cbl-b . Subsequent bioassay-guided isolation of extracts provided seven prenylated spermidine or spermine derivatives, which were named sinularamides 1 – 7 .…”
Section: Cbl-b Immuno-oncology Agents In Preclinical and Clinic Studiesmentioning
confidence: 99%
“…Targeting this enzyme is a promising approach for the treatment of autoimmune diseases and cancer [ 126 , 127 ]. The Sinularamides A−G ( 107 − 113 ), isolated from the soft coral Sinularia sp., are a group of diterpenoids that inhibits Cbl-b enzyme [ 122 ]. The most potent of these compounds was the sinularamide C ( 109 ), displaying an IC 50 value in the low micromolar range ( Table 8 and Figure 9 ).…”
Section: Enzyme Inhibitors Isolated From Gorgonians and Soft Coralsmentioning
confidence: 99%